Multidisciplinary Diagnostic Challenges in Pediatric Functional Abdominal Pain: An Integrated Approach Across Diagnostic Radiology, Family Medicine, Nursing Practice, Public Health, Epidemiology, Clinical Pharmacy, Clinical Nutrition, and Surgical Special - Alamar, Abdullah Mastour; Raneem Khalid Altuwayrish; Rawan Ayidh Alqahtani; Amwaj Qassem Alqahtani; Abduljalil Salah Alahmadi; Saeed Ali Yahya Najmi; Muath Ali Aqeel Halawi; Saud Ahmad Sultan Turkistani; Mohammed Abdullah Mathkur; Rawan Hussein Ali Khawaji; Fares Zaban Alrowiliy (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Functional abdominal pain (FAP) is a prevalent pediatric condition characterized by recurrent or persistent abdominal discomfort without identifiable structural or biochemical abnormalities. Diagnosis relies on the Rome IV symptom-based criteria, emphasizing the gut–brain axis dysregulation and minimizing unnecessary investigations. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To summarize multidisciplinary perspectives on the etiology, epidemiology, clinical presentation, diagnostic evaluation, and management of pediatric FAP. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive narrative review of current evidence addressing biological, psychosocial, and environmental contributors to FAP, along with clinical guidelines for assessment and therapeutic approaches. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> FAP arises from a multifactorial interplay involving visceral hypersensitivity, altered gut microbiota, motility disturbances, and psychosocial stressors. The global prevalence is approximately 11.7%, with higher rates in females. Evaluation prioritizes history, physical examination, and identification of alarm features, whereas excessive testing offers limited diagnostic value. Effective management requires education, psychosocial interventions, lifestyle modifications, and selective dietary or pharmacological therapies. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> FAP is a chronic, multifaceted disorder requiring a biopsychosocial, multidisciplinary management strategy to restore function and improve quality of life.